Joachim de Fiore, the Franciscans and the Feasts of Holy Ghost - Lupi, João (Sententiae, 2025)
When Joachim de Fiore the Abbot from Calabria, exposed the doctrine of the trinitarian concept of History, he defended an idea that would be developed and have consequences just till our days, particularly in some countries which have Portuguese as their main language. The first and decisive influence was on Franciscan friars, named “the spirituals” who adapted it to the radical religious ideal of poverty and the abolishment of hierarchy in the Church. The theory of History of the Abbot Joachim was made real in the Feasts of the Holy Ghost which in Portugal took peculiar characteristics that cannot be found in any other Christian nation. Brazil received the so-called Feasts of the Divine through the immigrants of the Portuguese Azorean Archipelago, preserving them till nowadays and thus extending the vitality of Medieval Philosophy not only through the cult of the Holy Ghost but also by political Theology which is associated to it. The utopia of a New Age of peace and brotherhood is part of the Feasts and constitutes a philosophy of Brazilian culture.